Flexoelectric effect in cylindrical hybrid aligned nematic liquid crystals cell. Issue 5 (9th April 2019) - Li, Jianfei; Zhang, YanJun; Yue, Huairui; Dong, Shizhuo; Li, Xuan
ABSTRACT: The cylindrical cell is filled with hybrid aligned nematic (HAN) liquid crystal and boundary conditions of strong anchoring and weak anchoring are imposed on the inner and outer surfaces. Based on the elastic theory of liquid crystal and the variation method, we derive the equations for the bulk and boundary conditions of the cylinder. By computer simulation, the effect of flexoelectric on the director distribution under different flexoelectric coefficients and the dependence of the shift voltage on the applied voltage are obtained. The flexoelectric coefficients e 11 + e 33 and e 11 can affect the distribution of director. And a novel method to determine the flexoelectric coefficients by measuring the shift voltage is put forward. Graphical Abstract: